Signal Peptide-rheostat Dynamics Delay Secretory Preprotein Folding. Issue 19 (15th October 2022) - Smets, Dries; Smit, Jochem; Xu, Ying; Karamanou, Spyridoula; Economou, Anastassios
Graphical abstract: Highlights: Higher hydrophobicity drives partial helical structure formation in signal peptides. Partially helical structured signal peptide elevate dynamics in mature domain linkers. Highly hydrophobic signal peptides block mature domain folding and enhance secretion. Signal peptide effects are guided via their flexible C-region and the rheostat ( cis ). The rheostat also plays a role in guiding mature domain folding. Abstract: Sec secretory proteins are distinguished from cytoplasmic ones by N-terminal signal peptides with multiple roles during post-translational translocation. They contribute to preprotein targeting to the translocase by slowing down folding, binding receptors and triggering secretion. While signal peptides get cleaved after translocation, mature domains traffic further and/or fold into functional states. How signal peptides delay folding temporarily, to keep mature domains translocation-competent, remains unclear. We previously reported that the foldon landscape of the periplasmic prolyl-peptidyl isomerase is altered by its signal peptide and mature domain features. Here, we reveal that the dynamics of signal peptides and mature domains crosstalk. This involves the signal peptide's hydrophobic helical core, the short unstructured connector to the mature domain and the flexible rheostat at the mature domain N-terminus. Through this cis mechanism the signal peptide delays the formation of early initial foldons thus altering their hierarchy and delaying mature domain folding. We propose that sequence elements outside a protein's native core exploit their structural dynamics to influence the folding landscape.